Rowell's syndrome to ds-dna negative lupus nephritis: A yet unreported progression - Mayur R Bhobe; Swagata Tambe; Saurabh Jindal; H R Jerajani (Wolters Kluwer Medknow Publications, 2015)
Rowell's syndrome is now identified as a subtype of subacute lupus erythematosus (LE) with erythema multiforme-like skin lesions, positive serum rheumatoid factor, anti-Ro La positivity and speckled pattern of antinuclear antibodies. Here we describe a case of Rowell's syndrome in an 18-year-old female who was found to be ds-DNA negative, who later progressed to develop stage V lupus nephritis (LN) over a course of 4 months. Although extremely rare, most cases of LN are drug induced. Of only seven cases of non-drug induced LN with negative dsDNA, none had cutaneous involvement. Ours was a unique case of progression of Rowells syndrome to ds-DNA negative LN.